Appendectomy with a single incision laparoscopic surgery port made from a plastic bottle - Kanat, Burhan Hakan; Çay, Ferhat; Böyük, Abdullah; Girgin, Mustafa; Güneş, Bekir; İlhan, Yavuz Selim (My University, 2018)
Introduction: Although minimally invasive surgery offers great advantages to patients, it has certain disadvantages, such as dependence on technology, it is not always easily accessible, and greater expense.The aim of this study was to present a simple and inexpensive new technique for performing the minimallyinvasive surgery of a single-port laparoscopic appendectomy.Materials and Methods: The data of 6 patients who underwent single-port laparoscopic appendectomy usingthe mouth of a plastic bottle and a glove between January and November 2017 were evaluated retrospectively.Results: The mean age of the patients was 22.5±2.73 years (range: 19–27 years). Three patients weremale (50%) and 3 patients were female (50%). The mean duration of the operation was 61.8±5.52 minutes(range: 53–68 minutes). Two patients (33.3%) needed an additional port because manipulation could notbe achieved and a laparotomy was performed on 1 (16.6%) of these patients. There were no complicationsexcept for a wound site infection in 1 patient.Conclusion: While minimally invasive single-port laparoscopic surgery is successfully performed, it is amethod that has not yet become the gold standard, has a fairly long learning curve, and is diffiult to accessdue to fiancial and technical reasons. Simpler and cheaper methods using the same principle can be applied successfully, provided that they are performed by experienced hands.
Keywords: Cerrahi